A realização da experiência cristã da vida na Fenomenologia da Religião de Heidegger - Silva, Marcelo Ribeiro da (2020)
The theme of this paper is the comphreension of realization in the Christian experience of life in the Heideggerian interpretation of Paul Tarsus' epistles. In question it is the meaning of realization in the constitution of the fundamental meaning of religiosity, as the German philosopher Martin Heidegger (1889-1976) that appropriates the Pauline letters. The aim of the research is to understand phenomenologically the realizing meaning in the way of being of Christianity and, thus, to continue the Heideggerian enterprise (observed in his lectures on Phenomenology of religious life) in search of the fundamental meaning of Christian religiosity. For those we will be seek to understand the question of the factual life, in which the question is raised by the factual experience of the Christian life. Then, we will investigate how to take the phenomenon in the formal indication of its how, thus opening the way to access the phenomenon of proclamation and the constitutive realizing situation of Christian religiosity. Finally, Paul's own letters will look for the meaning of fulfillment in the facticity of the Christian life, especially in the original concepts: genesthai, parousia, kairós, and the Christian understanding of existence as a vigil. The work will observe the bibliographical research in the works of Martin Heidegger and Pauline epistles, also in their respective commentators related to the phenomenological thought. This endeavor means the continuation of a personal project to deepen the understanding of the Christian experience of life, it is also justified in the current demand to reconnect contemporary man with life in its facticity and adds the researches that are interested in the young Heidegger.